The Effect Of Wuluh Starfruit (Averrhoa bilimbi) and Srikaya Fruit (Anonna squamosa) Leaf Extracts On The Death Of House Cockroach (Periplaneta americana) - Kholilah Samosir; Tri Susanti; Annisa Pratiwi Putri (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
Cockroaches are residential pests that disturb the comfort of human life. Belimbing wuluh leaves and srikaya leaves can be used as natural bioinsecticides for cockroaches because they contain saponins, tannins, and alkaloids. Flavonoid compounds when inhaled can affect cockroach breathing and cause weakness in the nerves. This study aimed to determine the effectiveness of srikaya and belimbing wuluh leaf extracts on the death of house cockroaches. This type of research is Pre-Experimental. The research design is After Only Design. The samples used were 200 house cockroaches. There were 19 containers and 1 control each container containing 10 house cockroaches. The concentrations of belimbing wuluh and srikaya leaf extracts used were 30%, 35%, and 40%. The results of the T-test did not find a significant difference between c with a p-value = 0.638. The conclusion of this study, is that there is no difference between the use of starfruit leaves and srikaya leaves in the death of house cockroaches. Both extracts are equally effective in killing house cockroaches. Further research can be continued with other leaf extracts.